Novel Molecular Targets Participating in Myocardial Ischemia-Reperfusion Injury and Cardioprotection. (28th May 2019) - Liu, Nan-Bo; Wu, Min; Chen, Chen; Fujino, Masayuki; Huang, Jing-Song; Zhu, Ping; Li, Xiao-Kang
Abstract : Worldwide morbidity and mortality from acute myocardial infarction (AMI) and related heart failure remain high. While effective early reperfusion of the criminal coronary artery after a confirmed AMI is the typical treatment at present, collateral myocardial ischemia-reperfusion injury (MIRI) and pertinent cardioprotection are still challenging to address and have inadequately understood mechanisms. Therefore, unveiling the related novel molecular targets and networks participating in triggering and resisting the pathobiology of MIRI is a promising and valuable frontier. The present study specifically focuses on the recent MIRI advances that are supported by sophisticated bio-methodology in order to bring the poorly understood interrelationship among pro- and anti-MIRI participant molecules up to date, as well as to identify findings that may facilitate the further investigation of novel targets.